Three consecutive even integers can be represented by x, (x+2), and (x+4).
(x + (x + 2) + (x + 4)) - 10 = -22 Get rid of the parentheses
x + x + 2 + x + 4 - 10 = -22 Combine like terms (x + x + x) and (2 + 4 - 10)
3x - 4 = -22 Add 4 to both sides
3x = -18 Divide
x = -6
Check you work.
x = -6
x + 2 = -4
x + 4 = -2
(-6 - 4 - 2) - 10 = 22
-12 - 10 = -22
So, your three integers are -6, -4, and -2 .
Answer:
x=6
Step-by-step explanation:
The inverse is the equation with the x and y variables transposed
Answer:
-2.61803398875, -0.38196601125
or
(-3±√5)/2
Step-by-step explanation:
First, expand. (2x+3)² = 4x²+12x+9=5
4x²+12x+4 = 0
Quadratic equations take the form ax²+bx+c = 0
In this case,
a = 4
b = 12
c = 4
You can solve with the equation x=(-b±√b²-4ac)/2a
Plug in:
(-12±√144-64)/8
(-12±√80)/8
(-12±√2^4×5)/8
(-12±4√5)/8
(-3±√5)/2
Final answer x = (-3±√5)/2
If you want decimal form: -2.61803398875, -0.38196601125
Answer:C. 36
Step-by-step explanation: height is 12 base is 9
12^2+9^2= 144+81=225 sq rt of 225 =15
So 12+9+15=36